Long-Term Field and Horticultural Crops Intensification in Semiarid Regions Influence the Soil Physiobiochemical Properties and Nutrients Status - Agniva Mandal; Amardeep Singh Toor; Salwinder Singh Dhaliwal; Pritpal Singh; Vijay Kant Singh; Vivek Sharma; Raj K. Gupta; Rama Krishna Naresh; Yogesh Kumar; Biswajit Pramanick; Gangadhar Nanda; Ahmed Gaber; et al. (Agronomy, 2022)
The study was conducted to assess the long-term effects of predominant land uses on physicochemical properties, nutrient status and their interactions in soils of south-western Punjab representing the semi-arid soils of India. From each site, soil samples of three predominant land use viz. croplands, horticultural lands and uncultivated lands were collected from 0–15, 15–30, 30–60 and 60–90 cm depths. Soils of both croplands and horticultural lands were classified as sandy loam whereas uncultivated lands showed loamy sand texture with relatively higher pH, electrical conductivity (EC) and bulk density (Bd). Greater soil organic carbon (SOC), available nitrogen (N), phosphorus (P) and micronutrients (Zn, Cu, Fe and Mn) in horticulture might be due to the higher addition of OC and mineral nutrients through the decomposition of leaf litterfall and root deposits over their removal from soils while long-term use of potassic fertilizer raised the available K contents in croplands. Profile study up to 90 cm depicted the largest sequestration of 74.89 Mg C ha−1 under orchards which was 40 and 70% higher than croplands and uncultivated lands respectively. Significant variability in water-stable aggregates (WSA) (R2 = 0.5843, p < 0.05) and mean weighted diameter (MWD) (R2 = 0.6497, p < 0.01) with SOC indicated better soil stability in horticulture due to the presence of higher SOC. Positive relations of soil available micronutrients with SOC and finer soil particles were supported by the results of correlation, Principal component analysis and dendrogram indicating horticulture as a potent source of available micronutrients. An overall superiority of horticultural land use over the other two land uses in terms of nutrient status and soil stability suggests its inclusion as a positive strategy that could be taken into account in policymaking for maintaining productivity along with the sustainability of the concerned land degradation prone area.